Atlas of Cutaneous Lymphomas Classification and Differential Diagnosis - Carter, Joi B.; Carter, Joi B.; Goyal, Amrita.; Goyal, Amrita.; McDivitt Duncan, Lyn.; McDivitt Duncan, Lyn. (Springer International Publishing : Imprint: Springer, 2015)
The integration of clinical findings, laboratory results, and disease progression is critical for the diagnosis and treatment of patients with skin lymphoma. This atlas includes numerous clinical and histological images with diagrams, tables, and text describing each type of lymphoma in the current cutaneous classification scheme, which includes information on the recent classification scheme for cutaneous lymphoma published by the World Health Organization and the European Organization for Research and Treatment of Cancer Cutaneous Lymphoma Group.   Atlas of Cutaneous Lymphomas: Classification and Differential Diagnosis includes chapters on synonyms, clinical features (presentation, prognosis, and treatment), laboratory findings (histopathology, immunophenotype, and molecular), differential diagnosis, and presentation of clinical cases for each diagnostic entity. In addition, chapters are included on T-cell lymphomas, B-cell lymphomas, ancillary techniques including immunohistochemistry and molecular tests, and a glossary of terms. This book will help clarify the classification of cutaneous lymphoma and will serve as a useful tool for physicians involved in the diagnosis and treatment of patients with cutaneous lymphoma.